Teaching English to Students of Non-Linguistic Universities Based on a Competency-Based Approach (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The practice of teaching foreign languages in non-linguistic universities (a higher education institution where a foreign language is not a core language in the professional training system) reflects the history of changing approaches to teaching in search of the most effective scientific and methodological concept. However, changing approaches to teaching foreign languages in higher education must be considered in the broad context of what is happening in society in general and in the field of education in particular, since the need for reforms is due to the need to adapt the education system to the socio-economic needs of society.